Just the Kitchen. On Food Preparation in the Late Middle Ages and Early Modern Period - Anna Marciniak-Kajzer (Fasciculi Archaeologiae Historicae, 2024)
The paper, based on written sources as well as archaeological findings, points out that food preparation in the late Middle Ages and Early Modern Period required much more effort and skills. It also required more space and sometimes specialised rooms. The source records mention bakeries as well as cheese making and storage places, breweries and malt houses. These are usually separate buildings, functioning as back-of-house facilities. The former were located separately, most probably because of the fire hazard, and the latter perhaps because of the odours that were generated by the brewing process and the maturation or drying of the cheeses. Thus, instead of the single kitchen room that we are now accustomed to, on many farms, other rooms were used for food preparation and separate buildings that allowed for the production of the food and its preservation and safe storage. We need to take this into account when planning excavation studies of settlement assemblages dating from the time discussed here.